DIFFERENTIAL DIFFICULTY IN THE ACQUISITION OF SECOND LANGUAGE PHONOLOGY - Ellen Broselow; Zheng Xu (International Journal of English Studies (IJES), 2004)
This paper reports on Mandarin speakers' acquisition of English final voiced and voiceless obstruents and final labial nasals, none of which occur in Mandarin codas. The leamers' production patterns are compared with a simulation using the Gradual Leaming Algorithm (Boersma & Hayes 2001). We dernonstrate that when the Mandarin Chinese rankings are assumed as the initial state and this system is provided with representative English input, the GLA correctly models the order of acquisition of obstruent codas (voiceless before voiced). However, the GLA also predicts that voiced obstruent codas should be acquired before coda labials, which are less frequent than voiced obstruents in English. This prediction is not bome out; speakers made fewer errors with final labial nasals than with final voiced obstruents. We argue that Mandarin speakers' native language perception grammar makes perception of final obstruents more difficult than perception of final nasals, and conclude that the Mandarin learners' pattern can be understood with reference to perceived rather than absolute frequency of input structure types.